(untitled) (Research, Society and Development, 2022)
This article aimed to make a Systematic Literature Review (RSL) on the pedagogical practices used in the teaching-learning process of Physics, assisted by Virtual Laboratories. For the advancement of the research, we first tried to realize that related research was done and subsequently the RSL was done in the period between 2011 and 2021, in Portuguese and English. To this end, Parsifal is used, which is an online tool designed to support researchers in conducting systematic reviews of the literature. The RSL followed the protocol proposed by (Kitchenham, 2004), composed three steps, namely: planning execution and analysis of results. As results, it was found that most of the studies have the purpose of comparing the pedagogical performance of students comparing two groups (experimental and control) using pre-test and post-test without worrying about studying the effectiveness and efficiency of pedagogical practices used in the performance of experimental activities. Of the 28 articles analyzed, it was found that differentiated pedagogical practices were used and the one that stood out was the POE strategy (Predict, Observe and Explain) with a total of 7 articles.